Diabetes surveillance in Germany – strategy for the dissemination of results. (13th November 2019) - Reitzle, L; Paprott, R; Schmidt, C; Heidemann, C; Baumert, J; Du, Y; Scheidt-Nave, C; Ziese, T
Abstract: Background: Diabetes mellitus is a non-communicable disease with high public health relevance in Germany. Therefore, the Robert Koch Institute startetd to establish a national diabetes surveillance system in Germany in 2016. Essential part of a surveillance system is the dissemination of health information to the relevant stakeholders to facilitate its translation into action. Methods: For the development of the dissemination strategy, different sources of information were used. First, an online-survey combined with structured web-research explored dissemination approaches in the international context. Secondly, a workshop with public health experts from seven countries highlighted best practice examples. Based on this information, a dissemination strategy was developed in close alignment with the scientific advisory board of the diabetes surveillance including experts from politics, prevention research, regional health reporting, physicians/diabetologists and public health scientists. Results: Three main questions were identified to be considered in the dissemination of health information: Which audience group is addressed? Which content is relevant to this group? What is the preferred format to communicate the information? Therefore, a diabetes report will be generated focusing on health policy makers summarizing the key information on the disease dynamic. A website containing all information including a visualization tool should facilitate access for stakeholders. Additionally, awareness needs to be raised using social media, classical media and direct interactions with relevant stakeholders. Conclusions: In alignment with different stakeholder groups, the diabetes surveillance developed a dissemination strategy considering international best practice examples and innovative ideas for health data visualization. The next steps are to refine the dissemination strategy based on feedback from the different stakeholder groups to ensure the use of the provided information. Key messages: A dissemination strategy for the diabetes surveillance has been developed in a participatory approach including experts from various stakeholder groups. Next steps include the refinement of the dissemination strategy and its formats based on stakeholders feedback requirements.